2020
DOI: 10.1371/journal.pone.0227781
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic parameters and the effect of a single and repeated doses of memantine on gastric myoelectric activity in experimental pigs

Abstract: Background Memantine, currently available for the treatment of Alzheimer's disease, is an uncompetitive antagonist of the N-methyl-D-aspartate type of glutamate receptors. Under normal physiologic conditions, these unstimulated receptor ion channels are blocked by magnesium ions, which are displaced after agonist-induced depolarization. In humans, memantine administration is associated with different gastrointestinal dysmotility side effects (vomiting, diarrhoea, constipation, motor-mediated abdominal pain), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Higher donepezil concentration in the pituitary compared the other brain regions suggests a role of the blood–brain barrier protection and active efflux mechanisms. In contrast to memantine, where the highest concentrations were found in the hippocampus and medulla [ 15 ], donepezil accumulated mainly in the medulla and medulla oblongata.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher donepezil concentration in the pituitary compared the other brain regions suggests a role of the blood–brain barrier protection and active efflux mechanisms. In contrast to memantine, where the highest concentrations were found in the hippocampus and medulla [ 15 ], donepezil accumulated mainly in the medulla and medulla oblongata.…”
Section: Discussionmentioning
confidence: 99%
“…A markedly higher concentration of donepezil was found in the liver, which indicates a possible first pass effect, the proportion of active metabolite accounted for was 34%. In many aspects, the pharmacokinetic profile of donepezil follows similar patterns to memantine after intragastric administration [ 15 ], where highly perfused organs and organs of elimination (lung, kidney, liver) contained high concentrations of the drug. Donepezil also accumulated in the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface electrogastrography (EGG) is a non-invasive method for the assessment of gastric myoelectrical activity [ 27 , 28 , 29 , 30 , 31 , 32 ]. Our group has demonstrated that EGG is also reliable in experimental pigs [ 26 , 33 ]. Porcine surface EGG is fully comparable with that one recorded in healthy humans [ 34 ].…”
Section: Introductionmentioning
confidence: 99%